Thermophilic methane fermentation of chicken manure in a wide range of substrate moisture contents - Salyuk, Anatoly; Zhadan, Sergiy; Shapovalov, Yevhenii (My University, 2015)
One of the effective ways of environmental management in poultry waste that allows the increase of energysaving and reduction of negative environmental impact is methane fermentation. Methane fermentation process is possible in three temperature modes: psychrophilic, mesophilic and thermophilic. Methane fermentation of chicken manure in thermophilic mode is less studied in comparison with mesophilic mode. The article presents the results of the study of methane fermentation of these wastes. The process was carried out in thermophilic conditions at 50 °C. Substrate moisture values varied from 72% to 99%. Biogas production ranged from 10,6 ml / g VS to 382,3 ml / g VS, methane production – from 1,8 ml / g VS to 207,9 ml / g VS. The maximum yield of biogas and methane per unit of mass was reached with the substrate moisture content of 92%. Production of methane from chicken manure in the thermophilic mode with low moisture level of the substrate was also possible despite the high content of ammonia nitrogen and free ammonia. However, with a decrease of the substrate moisture content lower than 80% efficiency of methane fermentation was at the same level and very low/
Keywords: кафедра харчової хімії; chicken manure; anaerobic digestion; biogas; ammonia; inhibition